2002
DOI: 10.1046/j.1464-5491.2002.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hormone replacement therapy on inflammation‐sensitive proteins in post‐menopausal women with Type 2 diabetes

Abstract: These findings indicate that oral HRT with conjugated equine oestrogen plus medroxyprogesterone acetate increases plasma CRP levels but not necessarily global inflammatory activity in post-menopausal diabetic women. An increase in plasma CRP may potentially increase risk of a cardiovascular event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…Whether this represents a fundamental biological process between sexes or more probably is a reflection of a different pattern of confounding between men and women is uncertain. In an attempt to examine the latter, we investigated whether hormone replacement therapy (HRT) could be one such sex-linked confounding factor, since HRT is associated with increased CRP levels in women [39]. However, the positive CRP-diabetes association in women could not be explained by use of oestrogen or HRT.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this represents a fundamental biological process between sexes or more probably is a reflection of a different pattern of confounding between men and women is uncertain. In an attempt to examine the latter, we investigated whether hormone replacement therapy (HRT) could be one such sex-linked confounding factor, since HRT is associated with increased CRP levels in women [39]. However, the positive CRP-diabetes association in women could not be explained by use of oestrogen or HRT.…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been shown to increase after HRT (Manning et al 2002), but CRP concentrations were not increased following supplementation in the ISOHEART study, and therefore isoflavones do not appear to mimic oestrogen action, at least as far as the effects on CRP are concerned. On the contrary, although the data for CRP was highly skewed and the statistical processing was problematic, thorough statistical analysis of the data by logistic regression has demonstrated that isoflavone consumption has a beneficial effect on CRP concentrations compared with the placebo treatment (see Hall et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…HRT has been suggested to decrease cell adhesion molecules (Koh et al 1997) and endothelin 1 (Wilcox et al 1997) concentrations. However, recent reports have shown adverse effects of HRT on the vasculature, including increased concentrations of CRP (Cushman et al 1999;Manning et al 2002) and increased risk of thrombosis (Nelson et al 2002). In addition to the latter, the reported association between hormonedependent cancers and HRT (Beral et al 2005), as well as unexpected reports of increased CVD rates with HRT (Grady et al 2002), has led to investigation of alternative therapies to counteract oestrogen deficiency at menopause.…”
Section: Cvd and Menopausementioning
confidence: 99%
See 1 more Smart Citation
“…interleukina 6 (IL-6), pozostają niezmienione pod wpływem HTZ, zarówno w grupie kontrolnej, jak i u pacjentek chorych na cukrzycę [31,32].…”
Section: Hormonalna Terapia Zastępcza U Pacjentek Chorych Na Cukrzycęunclassified